Spectroscopic determination of intracellular quercetin uptake using erythrocyte model and its implications in human aging - Kumar, Prabhanshu; Wadhwa, Ridhima; Gupta, Riya; Chandra, Pranjal; Maurya, Pawan Kumar (3 Biotech, 2018)
The present study was carried out to detect intracellular quercetin uptake by RBCs during human aging. The study was carried out on 95 normal healthy subjects of both the sexes. Intracellular quercetin uptake was estimated by performing ethyl acetate extraction. A significant ( p < 0.001) decline in intracellular quercetin uptake by human RBCs was observed in elderly as compared to young population, while plasma membrane redox system (PMRS) activity was significantly decreasing as a function of human age. To the best of our knowledge, we are the first to present quercetin uptake by erythrocytes during aging in humans with this study. It is hypothesized that intracellular uptake of quercetin may serve as an intracellular electron donor for plasma membrane redox system in red blood cells during cellular aging which plays an important role in extracellular dehydroascorbate reduction and ascorbate recycling.